MATHEMATICAL AND STATISTICAL ANALYSIS OF INFLUENCE OF ENVIRONMENTAL FACTORS ON THE PERIODONTAL STATUS IN CHILDREN FROM DIFFERENT ECOLOGICAL REGIONS OF UKRAINE - O.I. Ostapko (Український стоматологічний альманах)
Actuality. Technogenic impact to the ecosystem increases in Europe and world, which causes high levels of ecologically dependent pathology among children. Dental and general somatic health is formed under the influence of the same environmental factors. Therefore, analyzing and improving knowledge about the adverse effects of environmental factors on the formation of the dental health of children is necessary for risk assessment, forecasting changes in the morbidity and development of preventive measures designed taking into account regional peculiarities, timely prevention and correction of initial changes.